1999
DOI: 10.1086/314680
|View full text |Cite
|
Sign up to set email alerts
|

Early Immune Activation in Acute Dengue Illness Is Related to Development of Plasma Leakage and Disease Severity

Abstract: T lymphocyte activation and increased cytokine levels have been described in retrospective studies of children presenting with dengue hemorrhagic fever (DHF). Serial plasma samples obtained in a prospective study of Thai children presenting with <72 h of fever were studied. Plasma levels of 80-kDa soluble tumor necrosis factor receptors (sTNFRs) were higher in children who developed DHF than in those with dengue fever (DF) or other nondengue febrile illnesses (OFIs) and were correlated with the degree of subse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
253
3
3

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 337 publications
(283 citation statements)
references
References 40 publications
24
253
3
3
Order By: Relevance
“…As predictors of DHF, previous studies have proposed certain host factors such as soluble tumour necrosis factor receptors and soluble vascular cell adhesion molecule-1 and dengue virus non-structural protein NS1 [26][27][28]. An increased level of PAIgM during the acute phase of a secondary infection was highly specific for the development of DHF (92·1%) in this study, although its sensitivity was relatively low (48·6%).…”
Section: Discussioncontrasting
confidence: 43%
“…As predictors of DHF, previous studies have proposed certain host factors such as soluble tumour necrosis factor receptors and soluble vascular cell adhesion molecule-1 and dengue virus non-structural protein NS1 [26][27][28]. An increased level of PAIgM during the acute phase of a secondary infection was highly specific for the development of DHF (92·1%) in this study, although its sensitivity was relatively low (48·6%).…”
Section: Discussioncontrasting
confidence: 43%
“…Lack of iNKT cells greatly ameliorated DENV-associated disease including vascular leakage syndrome, a hallmark of se-vere DENV infection in humans. 6,8 Increased hematocrit, a marker of hemoconcentration, and Evans blue leakage were strongly reduced in DENV-infected J␣18 Ϫ/Ϫ mice compared with infected WT mice. In parallel, histologic examination of liver sections revealed that, compared with WT mice, infected J␣18 Ϫ/Ϫ developed less acute disease.…”
Section: Discussionmentioning
confidence: 98%
“…1,5,6,8 -10,56 Inasmuch as vascular leak syndrome is a hallmark of severe DENV infection in humans, 6,8 we measured hematocrit and Evans blue permeability in DENV-infected WT and J␣18 Ϫ/Ϫ mice. Compared with mock-treated mice, the hematocrit concentration was higher at day 5 after infection in DENV-infected WT animals ( Figure 3A).…”
Section: Mice Deficient In Inkt Cells Survive To Lethal Denv Challengementioning
confidence: 99%
See 1 more Smart Citation
“…Another study found the ratio of TNF-α-to IFN-γ-producing cells was higher when DENV-specific CD4 + T cells were stimulated ex vivo with antigens from the heterologous vs. homologous serotype (18). Increased TNF-α production by T cells could facilitate vascular leakage, as TNF-α has been detected more frequently and at higher levels in the serum of patients with DHF/DSS than with DF (19). Overall, studies in human DENV infections thus far have mostly focused on the potential role of T cells in pathogenesis and the association between HLA alleles and disease severity.…”
Section: A Protective Role For Original Antigenic Sinmentioning
confidence: 99%